A comprehensive work package for energy storage systems as a means of frequency regulation with increased penetration of photovoltaic systems. (September 2019) - Tang, Zhi Xuan; Lim, Yun Seng; Morris, Stella; Yi, Jia Liang; Lyons, Padraig F.; Taylor, Phil C.
Highlights: A work package of energy storage system for grid frequency regulation is proposed. The package includes grid network modeling, ESS sizing, and control algorithms. The proposal shows ESS is able to maintain frequency under photovoltaic systems. The required cyclical operation of ESS for frequency regulation remains a concern. The modularity design of the test system allows various permutations to be tested. Abstract: Grid frequency deviation occurs due to the power mismatch and is corrected by a series of control actions carried out by the generators. At present, the correction of the frequency deviation is limited by the ramp rates of generators, which depend on the inertia of their rotating masses. Under the increasing penetration of intermittent renewable energy sources, the task of frequency regulation becomes more demanding in terms of response times due to the frequent power mismatches and reduction of system inertia. An energy storage system (ESS) can be an effective means of regulating the frequency due to its general fast response characteristics. A comprehensive work package is developed in MATLAB/Simulink and Matpower to study how ESS can handle the rapid changes of frequency continuously within a specified window of its state of charge (SOC). This paper includes an IEEE 24-Bus grid network modeling, the sizing of ESS and also proposes ESS controllers with offset control algorithms as the sustainable solution for frequency regulation. As such, the modularity design of the test system allows various types of ESS or loads to be tested. The locations for ESS to be placed on the network are also identified for the best frequency regulation response without causing any grid voltage violations. Meanwhile, the scenarios of high penetration of photovoltaic systems and undersized ESS are also investigated. The results indicate that ESS is able to maintain the grid frequency under the intermittency of photovoltaic systems continuously.